Penggunaan Metode Total Physical Respon Untuk Melatih Kemampuan Berbicara Bahasa Arab Siswa - Fahrurrozi, Imam (STAI Nurul Huda Kapongan Situbondo, 2021)
In the teaching and learning process, learning methods are important things that need to be considered by a teacher so that learning goes well and is not boring. Especially in learning Arabic which requires mastering four skills, the selection of methods must be appropriate to teach some of these abilities. Usually a teacher imposes a method to carry out learning, so what happens is that students are less enthusiastic about taking lessons. This study aims to determine the use of the Total Physical Response method to train students' Arabic speaking skills. The research method used is the Classroom Action Research method by applying two cycles. Each cycle includes action planning, implementation, observation, and evaluation activities. The results of the study indicate that to train students' speaking Arabic skills, it is necessary to equip students with a large vocabulary, and then the vocabulary is used to train students' speaking skills. The introduction of vocabulary in this study was carried out in the first cycle and the use of vocabulary in training students' speaking skills was carried out in the second cycle.